2000
DOI: 10.1021/bi9924765
|View full text |Cite
|
Sign up to set email alerts
|

Internal Loop/Bulge and Hairpin Loop of the Iron-Responsive Element of Ferritin mRNA Contribute to Maximal Iron Regulatory Protein 2 Binding and Translational Regulation in the Iso-iron-responsive Element/Iso-iron Regulatory Protein Family

Abstract: Iron-responsive elements (IREs), a natural group of mRNA-specific sequences, bind iron regulatory proteins (IRPs) differentially and fold into hairpins [with a hexaloop (HL) CAGUGX] with helical distortions: an internal loop/bulge (IL/B) (UGC/C) or C-bulge. C-bulge iso-IREs bind IRP2 more poorly, as oligomers (n ) 28-30), and have a weaker signal response in vivo. Two trans-loop GC base pairs occur in the ferritin IRE (IL/B and HL) but only one in C-bulge iso-IREs (HL); metal ions and protons perturb the IL/B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 46 publications
5
64
0
Order By: Relevance
“…1), which differs from human ferritin-L and frog ferritin IRE only by having a C-G closing base pair rather than a U-G, the G 26 residue, also in the internal loop region of the IRE, was not protected by yohimbine from oxidation. This result is consistent with the observation that G 26 and G 27 exhibit different environments when probed by NMR and metal-binding studies (43). The native fluorescence of yohimbine was also used to study binding to the IRE.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1), which differs from human ferritin-L and frog ferritin IRE only by having a C-G closing base pair rather than a U-G, the G 26 residue, also in the internal loop region of the IRE, was not protected by yohimbine from oxidation. This result is consistent with the observation that G 26 and G 27 exhibit different environments when probed by NMR and metal-binding studies (43). The native fluorescence of yohimbine was also used to study binding to the IRE.…”
Section: Resultssupporting
confidence: 88%
“…In contrast, addition of Hoechst 33258, which is well known to bind nucleic acids (49), inhibited ferritin synthesis by Ͼ50% (data not shown). As shown in this (see supporting information) and earlier work (16,43), a G 18 A mutation in the ferritin IRE (G 18 forms a base pair with C 14 in the IRE terminal loop) (33, 34) displays a reduced affinity for IRP (16,43), which increases ferritin mRNA translation. Translation of mRNA with the G 18 A mutation in the IRE was unaffected by yohimbine (Fig.…”
Section: Acceleration Of Ferritin Synthesis By Yohimbinesupporting
confidence: 65%
“…Third, genetic ablation of both IRPs in intestine dramatically increased ferritin and ferroportin protein levels yet only modestly increased m-acon protein, apparently because ferritin and ferroportin mRNA translation are more strongly repressed by IRP action . These findings, along with the observation that IRPs appear to differentially interact with the ferritin and m-acon IREs, suggest that IREs differ in their regulatory potential for dictating control of mRNA translation Ke et al 2000). In this study, we focused on determining if an RNA binding hierarchy exists between IRP1 and 59 IREs and what sequences within these regulatory elements modulate this hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal-sensitive quadruplexes have been shown to function as a protein synthesis rate regulator in a human mRNA (ADAM10;19,20). Our earlier studies showed direct binding of a number of nonferrous metal ions to IRE-RNA, such as Mg 2þ (21,22) and Mn 2þ (12) as well as complexes with Cu 1þ (21) and Ru 2þ (23).Regulation of stable mRNAs permits rapid cellular responses. Eukaryotic protein synthesis can be divided into three main phases: initiation, elongation, and termination.…”
mentioning
confidence: 99%
“…A large RNA surface remains exposed, inviting RNA interactions with other molecules and ions even while bound to IRP1. Probing IRE-mRNA with chemical cleavage agents such as Cu 1þ -1,10-phenanthroline or Mg 2þ (21,22) to locate metalsensitive sites, combined with the X-ray crystal structure of the IRE-RNA/IRP1 complex, shows that some metal sites are located on exposed RNA surfaces and are available for additional RNA interactions even in the IRP1 complex ( Fig. 1; 28).…”
mentioning
confidence: 99%